1998
DOI: 10.1152/ajpregu.1998.274.3.r596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous glucose and euglycemic insulin infusions on short-term appetite and food intake

Abstract: To investigate the short-term effects of insulin on feeding, 14 fasting, young adults received 150-min euglycemic intravenous infusions of control (C), low-dose (LD, 0.8 mU ⋅ kg−1 ⋅ min−1), and high-dose (HD, 1.6 mU ⋅ kg−1 ⋅ min−1) insulin and ate freely from a buffet meal during the last 30 min. Steady-state preprandial plasma insulin concentrations were 5.9 ± 0.7 (C), 47 ± 2 (LD), and 95 ± 6 (HD) μU/ml and increased 56–59 μU/ml during the meal. No effect of treatment type on hunger or fullness ratings, durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 27 publications
3
58
1
Order By: Relevance
“…The decrease in plasma glucose may not reach hypoglycemic levels, but still give an uncomfortable feeling. It has been shown that minute variations in glucose concentrations can influence feelings of hunger and satiety (Chapman et al, 1998;Gielkens et al, 1998). However, we were not able to detect any increased variability in the peripheral glucose levels measured in subcutaneous adipose tissue in the sensitive subjects.…”
Section: Discussioncontrasting
confidence: 91%
“…The decrease in plasma glucose may not reach hypoglycemic levels, but still give an uncomfortable feeling. It has been shown that minute variations in glucose concentrations can influence feelings of hunger and satiety (Chapman et al, 1998;Gielkens et al, 1998). However, we were not able to detect any increased variability in the peripheral glucose levels measured in subcutaneous adipose tissue in the sensitive subjects.…”
Section: Discussioncontrasting
confidence: 91%
“…Previously, euglycemic infusion of insulin in humans has been shown not to affect appetite regulation, suggesting that insulin does not enhance satiety under these circumstances. 38 However, this does not exclude the possibility of an interactive effect on appetite regulation mediated by insulin in combination with post-meal increase in plasma glucose or the release of intestinal hormones. Nor can a hepatic effect induced by the high portal insulin concentration following meal ingestion be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Nor can a hepatic effect induced by the high portal insulin concentration following meal ingestion be excluded. 38 In addition, intracerebroventricular administration of insulin has been shown to reduce energy intake in baboons. 39 The present observation strengthens the hypothesis that insulin plays an important role in appetite regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, aging is also associated with changes in glucose metabolism due to increasing insulin resistance, and amylin may merely be acting as a marker of impaired glucose metabolism. Insulin is unlikely to play a role in the anorexia of aging in humans since insulin infusions within the physiologic range fail to alter food intake (Chapman et al 1998). …”
Section: Gastrointestinal Hormonesmentioning
confidence: 99%